(untitled) (Educação e Pesquisa, 2023)
The inclusion of students with disabilities in professional and technological education (PTE) has made important advances in recent years, such as the implementation of public policies. One of them is Law n. 13,409/2016, which guarantees people with disabilities the right to vacancies in the admission processes, a decision that affected the increase of 114.1% in special education (SE) enrollment in the four-year period 2016-2020. This investigation aimed to analyze the guiding policies for the PTE students with disabilities in three Federal Institutes (FIs) in the state of Rio Grande do Sul in compliance with the current SE national guidelines. With regard to the method, it is qualitative approach research and a case study type, whose elements were submitted to hermeneutic analysis, developed in three aspects: 1) admission; 2) learning and permanence; and 3) participation and protagonism. The results show that the policies of the three institutions comply with current national legislation, but there is a need to create programs to outline effective actions aimed at students with disabilities. It is noteworthy that the PTE specificities and the institutions territoriality are included in the documents in a restricted way. Finally, there is clearly a need to make national policies that bring together the FIs, promoting joint actions in the perspective of inclusive education.